Chymase expressing bone marrow mast cells in mastocytosis and myelodysplastic syndromes: an immunohistochemical and morphometric study. Issue 2 (1st February 2003) - Horny, H-P; Greschniok, A; Jordan, J-H; Menke, D M; Valent, P
Abstract : Background: Two cell specific neutral proteases, tryptase and chymase, are produced by human mast cells (MC). Tryptase is constitutively expressed by all MC, whereas chymase is found only in an MC subset. Very little is known about chymase expression in MC proliferative disorders (mastocytosis). Aims and Methods: Routinely processed, formalin fixed, and paraffin wax embedded bone marrow trephine biopsy specimens obtained from patients with various subtypes of mastocytosis (n = 47) and myelodysplastic syndromes (MDS; n = 28) were immunostained with antibodies against chymase and tryptase. Normal/reactive bone marrow specimens with intact haemopoiesis (n = 31) served as controls. The numbers of chymase expressing (C+) and of tryptase expressing (T+) MC were assessed morphometrically using a computer assisted video camera system. Results: In normal/reactive bone marrow, the numbers of C+ MC (median, 8/mm 2 ; maximum, 159/mm 2 ) were in the same range as those of T+ MC (median, 4/mm 2 ; maximum, 167/mm 2 ). Because normal MC express both chymase and tryptase, these findings indicate that the common phenotype of bone marrow MC in normal/reactive states is MCTC (MC expressing both tryptase and chymase). In contrast, in MDS and mastocytosis, the bone marrow exhibited far more T+ MC than C+ MC in almost all cases. Conclusions: According to these findings, the predominant MC type in the bone marrow in neoplastic states such as MDS and mastocytosis is MCT (MC expressing only tryptase). Although the pathophysiological basis of this apparent lack of chymase expression in most neoplastic MC in mastocytosis and MC involved in MDS remains unknown, this study has produced further evidence of the superior value of antitryptase antibodies in the diagnosis of mastocytosis.